(untitled) (Nigerian Journal of Technology, 2021)
Soil behaviour may be hinged on the relative composition and nature of arrangement of the various component fractions embedded in the soil. Whether the component proportions of the fines (silt/clay) are interwoven within the voids of coarse (sand) grains, or that the coarse grains are dispersed within the fines mass would determine sandy or clayey soils characteristics. Density and voids ratio assessments of tropical residual soils were conducted in this study on compacted reconstituted binary blends of fines and coarse soils which were also subjected to cycles of sustained compression loads. The soil was separated into fines and coarse fractions by sieving through a 75 µm sieve. Reconstituted soil samples were prepared from these two fractions in varying percentages ranging from zero fines content (0:100) to 100 percent fines fraction (100:0) in 10 percent increment. The results indicate that the moisture contents and changes in density due to moisture movements were insignificant for fines less than 40 percent. Compacted density and voids ratios were optimally maximum and minimum with values of about 2000kg/m^3 (dry density) and 0.2 respectively at fines contents of 20 percent. An optimal degree of saturation was also obtained at 20 percent fines. Optimum moisture contents were also obtained at about 30 percent with the corresponding optimum dry densities ranging from 2100kg/m^3 to 2200kg/m^3 from compression tests. The thresholds fines content therefore would depend on the stress state of the soil and may be about 20 or 30percent for subgrade assessments or geotechnical considerations respectively and beyond the threshold fines content the fines fraction makes up the stress-carrying matrix for the soil mass thus controlling the soil behaviour. http://dx.doi.org/10.4314/njt.v40i3.3